2019
DOI: 10.1038/s41598-019-42667-z
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic insights into effects of wheat straw compost fertiliser application on microbial community composition and function in tobacco rhizosphere soil

Abstract: The application of fertilisers incorporated with plant residues improves nutrient availability in soils, which shifts the microbial community structure and favours plant growth. To understand the impact of wheat straw compost fertiliser on soil properties and microbial community structure, tobacco planting soils were treated with four different fertilisers using varied amounts of straw compost fertiliser and a no fertiliser control (CK). Results showed that different fertilisers affected available soil nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…No special agronomic practices have been adopted at the flue-cured tobacco-planting sites sampled in this study. The amount of fertilizers applied often differs because the basic fertility of the soil and the demand of crops are usually considered when applying fertilizer in the field 21,25,27 . In addition, although the irrigation method used can affect the quality of flue-cured tobacco, the methods are not determined by the cultivars but by the sources of available water 23 .…”
Section: Effects Of Climatic and Soil Factors On The Yield And Qualitmentioning
confidence: 99%
“…No special agronomic practices have been adopted at the flue-cured tobacco-planting sites sampled in this study. The amount of fertilizers applied often differs because the basic fertility of the soil and the demand of crops are usually considered when applying fertilizer in the field 21,25,27 . In addition, although the irrigation method used can affect the quality of flue-cured tobacco, the methods are not determined by the cultivars but by the sources of available water 23 .…”
Section: Effects Of Climatic and Soil Factors On The Yield And Qualitmentioning
confidence: 99%
“…Ample evidence has accumulated in recent years that the quantity and quality of soil organic matter can significantly affect the composition of soil microbial community [28][29][30] , which is often represented by the phenomenon that soils with high organic matter content tend to have higher microbial community diversity 31,32 . In our study, both the Chao 1 index and the Shannon index in the M treatment were lower than that in the NM treatment Paired T-test DF = 2, t = 0.27 p = 0.8140 DF = 2, t = −2.08 p = 0.1732 DF = 2, t = −8.12 p = 0.0148 DF = 2, t = −2.77 p = 0.1096 DF = 2, t = −3.32 p = 0.0800 DF = 2, t = 0.65 p = 0.5799 DF = 2, t = 0.80 p = 0.5083 DF = 2, t = −1.73 p = 0.2254 DF = 2, t = −1.30 p = 0.3227 www.nature.com/scientificreports www.nature.com/scientificreports/ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from agrarian soils confirmed that there are high microbial stock and plant development promotion pursuits [79]. Many studies are showing the latest metagenomic improvements in agriculture [76][77][78]. Soil microbes play a crucial part for triggering the plant development, stress reactions, as well as defense in vegetation [80,81].…”
Section: Metagenomics For Sustainable Agricultural Practicesmentioning
confidence: 99%
“…The latest advances in the soil metagenomics emerge as an extraordinary area of research because of the assignment of understanding the associated microorganisms in development and plant growth [75,76]. Likewise, restoration of the microbial population was determined to improve grain yield as well as soil health [77]. Metagenomics can predict the soil microbes' structure and the impact on microbial groups of connected niches [9,35].…”
Section: Metagenomics For Sustainable Agricultural Practicesmentioning
confidence: 99%